Low FT3 is a valuable predictor of severe acute pancreatitis in the emergency department. Issue 7 (3rd July 2018) - Yang, Wei Qiang; Yang, Qian; Chen, Wan Jun; Zhang, Xiao Bin; Xu, Qing Qing; Qiao, Yun; Xu, Xin Hui; Liu, Li; Lu, Xiao Ye; Zhu, Chang Qing
Abstract : OBJECTIVE: To investigate the relationship between serum levels of thyroid hormones and disease severity at the early stage of acute pancreatitis (AP). METHODS: Cohort data from 172 patients with AP attending the Emergency Department of our hospital from 2012 to 2017 were retrospectively reviewed and analyzed. Patients were categorized into mild (MAP), moderately severe (MSAP) and severe AP (SAP) groups based on the disease severity. The MSAP and SAP groups were combined into a non‐MAP group for analysis. The predictive values of C‐reactive protein (CRP) levels, Ranson score, APACHE II score and serum thyroid hormone levels were analyzed. RESULTS: In total, 76 (44.2%), 85 (49.4%) and 11 (6.4%) patients were included in the MAP, MSAP and SAP groups, respectively. The free triiodothyronine (FT3) levels were significantly lower in the combined non‐MAP group than in the MAP group. The tetraiodothyronine (T4) levels were significantly lower in the SAP group than in the MAP and MSAP groups ( P  = 0.002). Logistic regression analysis revealed that a low FT3 level was an independent risk factor for the incidence of non‐MAP ( P  = 0.004). The area under the receiver operating characteristic curve and sensitivity of FT3 were 0.729 and 88.2%, respectively, which were higher than those of CRP, Ranson and APACHE II scores. CONCLUSION: Monitoring FT3 levels in the early stage of AP is helpful for evaluating disease severity and predicting the incidence of non‐MAP, making it a useful tool for guiding AP treatment.